Development of Instruction – Augmenting Project for Faculty Members of the Department of Management Studies: An Action Research - Vitobina, Crugie Boy A.; Ronas, Sunny May S.; Navales, Bhrendelyn B.; Dela Rea, Kirk T. (Future Science / FSH-PH Publications, 2023)
This study aimed to assess the developed e-class record system to help the academic staff of the Cavite State University – CCAT Campus. The researchers wanted to evaluate the said system to determine the effectiveness and ease of use of the e-class record system. This study employed quasi-experimental and phenomenological designs to understand user experience to augment the Technology Acceptance Model (TAM). The intervention employed by the researchers was efficient and saved 0:25:51 of time in minutes, as indicated by the average cumulative usage time of 58:20.8 minutes. The goal of setting the intervention was to use e-class records, which had the desired result. This action research revealed the efficiency with regard to the time stamping with intervention, which helped the faculty improve their target goal of efficiency in recording grades. This study recommended having more knowledge and learning among the faculty using the said e-class record system.